2017
DOI: 10.1055/s-0037-1606383
|View full text |Cite
|
Sign up to set email alerts
|

Fresh versus Frozen Embryo Transfer in PCOS: Arguments for and Against

Abstract: In vitro fertilization (IVF) is a common infertility treatment for women with polycystic ovarian syndrome (PCOS) who have failed to conceive in ovulation induction and who have other concomitant infertility factors. Women with PCOS tend to have an excess response to ovarian stimulation during IVF. Freeze-all strategy with deferred frozen embryo transfer was initially used to prevent ovarian hyperstimulation syndrome (OHSS) in patients with a high risk. New evidence from randomized trials showed elective frozen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The early-onset of OHSS is related to exaggerated ovarian response to gonadotrophin stimulation and administration of hCG, while the late-onset is related to the endogenous hCG from trophoblast where conception occurs [ 5 ]. To prevent OHSS, freezing all embryos and waiting for a suitable time for embryo transfer are proposed [ 6 ]. Indeed, a randomized clinical trial with a large sample size showed that women with PCOS who underwent frozen-embryo transfer (FET) had a lower incidence of OHSS (1.3% vs. 7.1%) and pregnancy loss (22% vs. 32.7%) and a higher rate of live birth (49.3% vs. 42%), compared with women with PCOS underwent fresh embryo transfer cycles [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early-onset of OHSS is related to exaggerated ovarian response to gonadotrophin stimulation and administration of hCG, while the late-onset is related to the endogenous hCG from trophoblast where conception occurs [ 5 ]. To prevent OHSS, freezing all embryos and waiting for a suitable time for embryo transfer are proposed [ 6 ]. Indeed, a randomized clinical trial with a large sample size showed that women with PCOS who underwent frozen-embryo transfer (FET) had a lower incidence of OHSS (1.3% vs. 7.1%) and pregnancy loss (22% vs. 32.7%) and a higher rate of live birth (49.3% vs. 42%), compared with women with PCOS underwent fresh embryo transfer cycles [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a randomized clinical trial with a large sample size showed that women with PCOS who underwent frozen-embryo transfer (FET) had a lower incidence of OHSS (1.3% vs. 7.1%) and pregnancy loss (22% vs. 32.7%) and a higher rate of live birth (49.3% vs. 42%), compared with women with PCOS underwent fresh embryo transfer cycles [ 7 ]. To achieve a better pregnancy outcome, selective FET is considered a cost-effective treatment for those infertile women with PCOS in many IVF centers [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fresh ART cycles involve controlled ovarian stimulation, usually with high doses of gonadotrophin, to obtain multifollicular growth, but this, in turn, is linked to supraphysiological levels of estradiol and increased risk of ovarian hyperstimulation (OHSS) [ 84 ]. Consequently, all over the world, there is an increasing trend towards ‘freeze all’ cycles in ART practice [ 85 , 86 ], and a higher number of frozen embryo transfers are being performed to avoid the risk of OHSS and for endometrial optimization in subsequent cycles leading to oocyte retrieval. This might, to an extent, help to mitigate the burden of test failures and diagnostic errors due to low FF in the setting of ART.…”
Section: Challenges For Nipt In Art Pregnanciesmentioning
confidence: 99%
“… 10 , 22 As opposed to fresh cycles, frozen-thawed embryo transfer (FET) appears to provide a better and more physiological uterine environment for early implantation and fetal development. 23 , 24 In the context of the increasing adoption of FET globally, additional data would be more than welcome to explore whether the type of infertility cause may have any significant influence on birth outcomes resulting from FET cycles. The objective of this study was therefore to investigate the effect of infertility cause on perinatal outcomes when a freeze-all strategy was applied from a single center.…”
Section: Introductionmentioning
confidence: 99%